Competency-based learning (CBL) and animation-based learning: a comparative study on students’ academic achievement, interest and retention in auto mechanics - Nicholas Ude (Phd), Eze; Uzochukwu Peter, Obichukwu; Hillary Sunday, Nnadi (International Journal of Engineering and Technology, 2019)
A quasi experimental research design was adopted to compare competency-based learning and computer animation to determine their effect on academic achievement, retention and interest of students in auto mechanics. The pretest, posttest nonequivalent design was used. Six research questions were answered and four hypotheses were tested at 0.05 level of significance. Two technical colleges were used for the study. Population for the study was 115. Simple random sampling was used to assign school to treatment groups. No sampling was conducted in selection of students because intact classes were used. Auto mechanics Achievement Test (AMAT) and Auto mechanics Interest Inventory (AMII) were the instruments used for data collection. The data collected from the administration of the pretest and posttest was analyzed using Mean to answer the research questions while the hypotheses were tested at 0.05 level of significance using Analysis of Covariance (ANCOVA). The finding of the study revealed among others that students taught auto mechanics using competency-based Learning technique had higher retention and interest and a higher score in the achievement test than students taught using computer animation technique. The hypotheses tested showed that p < 0.05 implying a significant difference in the effect of a competency-based learning technique on the achievement score, retention score and interest of students taught auto mechanics. Based on the findings of the study, it was recommended that competency-based learning should be adopted for teaching of auto mechanics in the Technical Colleges since the course is project based.